"Overarching sustainability objectives overcome incompatible directions in the Common Fisheries Policy". (May 2018) - Goti-Aralucea, Leyre; Fitzpatrick, Mike; Döring, Ralf; Reid, David; Mumford, John; Rindorf, Anna
Abstract: The lack of clarity in the objectives of the Common Fisheries Policy (CFP) must be addressed to create a more efficient balance across diverse ecological, economic and social dimensions. Particularly economic and social objectives present at an overarching level must be made explicit and addressed in lower level management measures, in order to link them to biological objectives and allow policy to build a balance across types of objectives. Selecting clear objectives is essential, particularly for policy impact assessment. The aim of this paper is to demonstrate how more specific high level objectives to managing fisheries can be derived from stakeholders. The paper first reviews the definition of objectives, from a historical and conceptual perspective. Secondly, it discusses the issues of manageability and acceptability, and finally describes an articulation of the high level objectives derived from extensive stakeholder consultations at European and regional level. The results from workshops at the European level to identify objectives were further examined at regional level for the Baltic and North Seas in additional individual consultations. The German case addresses two seas (Baltic and North Seas), has a complex governance structure (due to federalism) and significant roles for the three types of actors (industry, government and environmental NGOs). The analysis suggests that establishing higher level sustainability objectives within the CFP can help diverse interest groups to develop a consensus on management actions to meet complex social goals. Highlights: High level policy objectives allow for synergies that are lost at lower level. Manageability and acceptability of objective is key for implementation and compliance. Limit values of some objectives can restrict the speed at which others are achieved. Participation of stakeholder in drafting objectives can lead to innovative approaches.